(untitled) (Research, Society and Development, 2021)
The present study aimed to evaluate adaptation of the single gutta-percha cone on root canal walls prepared with the two systems, the XP-endo Shaper (XPS; FKG Dentaire, La Chaux-de-Fonds, Switzerland) and ProTaper Next systems (PTN; Dentsply Sirona, Ballaigues, Switzerland) by using micro-computed tomography (micro-CT) technology. Twenty long oval-shaped canals in mandibular incisors were scanned by micro-CT (Skyscan 1172; Bruker microCT, Kontich, Belgium). Two groups were divided into (n = 10) according to the canal preparation protocol: XPS group with an extra 45 s of instrumentation and PTN group. A gutta percha cone, with respect to the protocol used for each group (size 40, .04 taper, XPS and size 40, .06 taper, PTN) was adapted to the canal at the working length of all the samples, and all root canals were filled, using the single-cone technique. The mean values for volume of voids and percentage relative to the mentioned space were correspondingly higher in XPS group than they were PTN group, mean values for volume of voids (3.61 mm3 - 1.92 mm3) and for percentage of voids (39.25% - 23.28%), respectively, significant differences were recorded (p < 0.05) between the two groups (XPS and PTN, Student’s-t test for homogenous variances and Mann–Whitney test). The canals prepared with XPS, in the procedure performed with an extra 45 s of instrumentation, showed a higher volume of voids than those prepared with the PTN system, in obturation of the root canal with the single cone technique.